Are patients more adherent to newer drugs? - Katharina E. Blankart; Frank R. Lichtenberg (Health Care Management Science, 2020)
The annual preventable cost from non-adherence in the US health care system amounts to 100 billion. While the relationship between adherence and the health system, the condition, patient characteristics and socioeconomic factors are established, the role of the heterogeneous productivity of drug treatment remains ambiguous. In this study, we perform cross-sectional retrospective analyses to study whether patients who use newer drugs are more adherent to pharmacotherapy than patients using older drugs within the same therapeutic class, accounting for unobserved heterogeneity at the individual level (e.g. healthy adherer bias). We use US Marketscan commercial claims and encounters data for 2008–2013 on patients initiating therapy for five chronic conditions. Productivity is captured by a drug's earliest Food and Drug Administration (FDA) approval year (“drug vintage”) and by FDA” therapeutic potential” designation. We control for situational factors as promotional activity, copayments and distribution channel. A 10-year increase in mean drug vintage is associated with a 2.5 percentage-point increase in adherence. FDA priority status, promotional activity and the share of mail-order prescription fills positively influenced adherence, while co-payments had a negative effect. Newer drugs not only may be more effective in terms of clinical benefits, on average. They provide means to ease drug therapy to increase adherence levels as one component of drug quality, a notion physicians and pharmacy benefit managers should be aware of.
Keywords: I12 Health Behaviour; 610; Medicines possession ratio; Innovation; Vintage; Promotion; Productivity in health care